Mechanical simulation of spring-based tube compensator - Trautmann, Laura; Piros, Attila; Szilágyi, Károly; Komáromi, Balázs (Design of Machines and Structures, 2024)
This article deals with the examination of a new product family of tube holders. FEA analysis and analytical calculation also provided information on displacements due to force. The article introduces a simplified mathematical model to substitute the compli-cated numeric simulations. The results have shown that appropriate calculations are accu-rate and can replace the simulation of fully detailed model.